Vigor of maize seeds determined by a free image analysis system - Medeiros, André; Pereira, Márcio; Silva, Íris Renata; Capobiango, Nayara; Flores, Milton Edgar (Revista Ciência Agronômica, 2019)
New and refined technologies based on computerized procedures create the potential for automating laboratory evaluations, constituting an alternative to reduce costs and increase the decision-making capacity regarding the destination of seed lots. The objective of this study was to evaluate the efficiency of the Sistema de Análise de Plântulas (SAPL®) free digital image processing software of seedlings in characterizing the physiological potential of maize seeds in comparison with information provided by vigor tests recommended for this species. Ten lots of maize seeds were submitted to germination, first germination count, germination speed index, seedling emergence, cold test and electrical conductivity. The results of these tests were compared with the data obtained from the image analysis, which evaluated the development of seedlings at three and five days counted from the beginning of the germination test, by obtaining values of seedling length, growth, development uniformity, vigor index and corrected strength index. SAPL® is a consistent and promising alternative for evaluating the physiological potential of maize seeds, presenting a high correlation of its variables with the traditional tests used. The evaluation can be performed on the third and fifth day after the germination test is installed.